Self-representation and Intercultural Acceptance in Comic Book Ma Voisine est Indonésienne - Firmonasari, Aprillia (Bina Nusantara University, 2023)
The research specifically examined French and Indonesian individuals’ representation from cognitive and interactional perspectives within sociocultural and sociocognitive contexts, mainly using dialogues in the comic book “Ma voisine est Indonésienne” (My Neighbor is Indonesian) by Emmanuel Lemaire. This comic strip was about the discovery of France through an Indonesian woman’s eyes and transcribes the two cultures’s encounters. The textual and structural aspects of the conversations were subject to analyses; their topical and situational dimensions were examined. NVIVO was used to support the qualitative analysis. The findings contribute to the development of a discourse analysis model of representation and perception of culturally based images or culturological models of communication, drawing heavily on Ulrike Niens’ social identity theory. The findings suggest that stereotypical conversations between the Indonesian and French characters in the comic book primarily occur within a social context, indicating that stereotyping is part of a complex dynamic process involving elements of subjectivity, collectivity, and intersubjectivity. These findings also reveal an unfavorable sociocultural representation of both Indonesian and French cultures, as 17 aggregated item codes demonstrate the representations of Indonesians are deemed unacceptable within French culture’s framework, while ten aggregated item codes indicate the representations of the French are deemed unacceptable within the Indonesian culture’s context. This implies language and cognition, influenced by prior experiences and societal norms, shape socialinteractions and contribute to stereotype creation.